Studi Penerapan Power Wheeling Pembangkit Fotovoltaik Dengan Metode MW-km - Muhammad Bhayu Bramantyo; Sasongko Pramonohadi; Sarjiya (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2024)
Efforts to mitigate carbon emissions within the electricity sector involve the implementation of environmentally sustainable renewable energy sources. Photovoltaic (PV) generation, functioning as a distributed generation (DG), represents a current trend in renewable energy installations. A distributed generation (DG) is situated near the load within distribution networks. When applied, a PV-DG influences the magnitude of power losses within existing electrical networks, subsequently impacting associated energy loss expenses. Additionally, adequate land availability is required for the PV-DG installation. The cooperation between PV-DG power providers and load partners is conducted remotely, resulting in distribution challenges. The construction of distribution lines by business actors to evacuate their electricity production is almost impossible. Distribution network rental emerges as an interesting solution, i.e., through a distribution network collaborative utilization scheme or power wheeling. This study seeks to examine the implementation of power wheeling of PV generation within the IEEE 33-bus distribution network system, by finding the location of the bus placement of the PV wheeling generation that results in the smallest total energy loss cost and distribution network rental cost. The MW-km method served as the basis for calculating network rental expenses. Moreover, this study incorporated the land availability associated with each bus. Findings indicate that positioning the PV wheeling generation at bus 8 yielded minimal total annual energy loss and distribution network rental costs. It indicates that the placement of a wheeling PV generation in arbitrary places does not necessarily result in the smallest total energy loss costs and distribution network rental costs.